Arrabidaea chica chloroform extract modulates estrogen and androgen receptors on luminal breast cancer cells - Douglas C. Brandão; Paula M. A. P. Lima; Isabella C. Martins; Carina S. Cordeiro; Antonielle O. Cordeiro; Lara Vecchi; Joyce F. C. Guerra; Priscila C. Orsolin; Matheus C. Gazolla; Danilo S. Costa; Ademar A. da Silva Filho; Thaise G. Araújo (BMC, 2022)
Abstract Background Breast Cancer (BC) is the most common cancer in women worldwide and, although 70% of patients are responsive to selective Estrogen Receptor (ER) modulators such as Tamoxifen (Tam), patients' survival is comprised by resistance to endocrine therapy. Brazilian flora, especially the Amazon biome, is one of the richest global sources of native species with potentially bioactive compounds. Arrabidaea chica is a plant native to the Amazon that has been used in the treatment of different diseases. However, its action on BC remains unclear. Methods Herein the biological effects of the chloroform extract of A. chica (CEAC) were evaluated on BC cells and in in vivo model. After confirmation of CEAC antioxidant capacity, cells were treated with CEAC and Tam, alone and with CEAC+Tam. The cell viability was evaluated by MTT and hormone receptor transcripts levels were assessed (ESR1, ESR2 and AR). Finally, anticarcinogenicity of CEAC was recorded in Drosophila melanogaster through Epithelial Tumor Test (ETT). Results The study confirmed the antioxidant activity of CEAC. CEAC was selective for MCF-7, downregulating ESR2 and AR transcripts and upregulating ESR2 expression. The modulatory effects of CEAC on ERs did not differ between cells treated with Tam and with CEAC+Tam. Interestingly, previous treatment with CEAC, followed by treatment with Tam promoted a significant decrease in cell viability. The extract also presented anticarcinogenic effect in in vivo assay. Conclusion The bioassays on breast tumor cells demonstrated the antiproliferative activity of the extract, which modulated the expression of hormone receptors and sensitized luminal tumor cells to Tam. These results suggest that CEAC could be a complementary treatment for BC.